2007
DOI: 10.1016/j.bbamcr.2006.06.013
|View full text |Cite
|
Sign up to set email alerts
|

ERM proteins in epithelial cell organization and functions

Abstract: ERM (Ezrin, Radixin, Moesin) proteins are membrane-cytoskeleton linkers that regulate the structure and the function of specific domains of the plasma membrane. ERM proteins are expressed in all metazoan analyzed so far. Genetic analysis of ERM protein functions has recently been performed simultaneously in three different organisms, mouse, Drosophila melanogaster and C. elegans. These studies have revealed a remarkable conservation of the protein functions through evolution. Moreover they have shed light on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
157
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 74 publications
3
157
0
2
Order By: Relevance
“…4 an enlargement of spots corresponding to the identified differentially expressed proteins is shown with the corresponding changes in expression rate. Among the proteins that we identified, by MS, as upregulated in both auranofin-and Auoxo6-treated cells are ezrin (spot G), associated with the cytoskeleton [38], peroxiredoxin 1 (spot I), a peroxidase with a high antioxidant efficiency implicated in regulating proliferation [39], differentiation, and apoptosis, and fragments of the heterogeneous nuclear ribonucleoprotein (spot F), which provides the substrate for the processing events that precursor messenger RNA undergoes before becoming functional [40]. This protein was also identified in spot A corresponding to the full protein.…”
Section: Proteomic Profiles Of Control and Gold-treated Cancer Cellsmentioning
confidence: 95%
“…4 an enlargement of spots corresponding to the identified differentially expressed proteins is shown with the corresponding changes in expression rate. Among the proteins that we identified, by MS, as upregulated in both auranofin-and Auoxo6-treated cells are ezrin (spot G), associated with the cytoskeleton [38], peroxiredoxin 1 (spot I), a peroxidase with a high antioxidant efficiency implicated in regulating proliferation [39], differentiation, and apoptosis, and fragments of the heterogeneous nuclear ribonucleoprotein (spot F), which provides the substrate for the processing events that precursor messenger RNA undergoes before becoming functional [40]. This protein was also identified in spot A corresponding to the full protein.…”
Section: Proteomic Profiles Of Control and Gold-treated Cancer Cellsmentioning
confidence: 95%
“…Recent genetic analyses revealed that ezrin is essential for the morphogenesis of epithelial cells (Fiévet et al, 2007). In ezrin Ϫ/Ϫ mice, morphological defects in the apical domain of intestinal and retinal pigment epithelial cells have been observed (Saotome et al, 2004;Bonilha et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The pERM proteins are restricted to the subapical compartment of polarized epithelia where they link the plasma membrane and the cytoskeleton (for review, see Ref. 13). Accordingly, pERM staining appeared in a subapical pattern colocalized with the actin band (Fig.…”
Section: Top: Control Cells (No H2o2) Showed Both Endogenous E-cad Anmentioning
confidence: 99%